Incretin – based therapy in diabetes mellitus: present scenario and expanding horizons (Nepal Journal of Epidemiology, 2016)
Let us hope that best is yet to come which is likely to bring us nearer to achieving our cherished goal of finding a cure of diabetes. I would like to sum up with an optimistic note by quoting Cristopher Reeve “So many of our dreams at first seem impossible, then they seem improbable, and then when we summon the will, they soon become inevitable ‘’.